Entrance door of the Garbhagriha of the Ganesha Temple - Temples of India Project Team (Jio Institute, 2024)
The entrance door of the garbhagriha (sanctum sanctorum) of the Ganesha Temple features multiple shakhas (vertical bands), which are plain. The garbhagriha is a small square chamber with the idol of Ganesha. The sanctum is devoid of any ornamentation except for the bharvahaka (load or weight bearer).